Vertical transport of HDPE microplastics through sandy and silty soil - Sayali Apte; Sangita Dike; Vaishnavi Dabir (Environmental Challenges)
Microplastic pollution is an emerging concern and poses a potential risk to soil ecosystems and subsequently can lead to groundwater contamination. The sandy and silty soils are the major soil types covering more than 31 % of the land area globally. The vertical transport of microplastic in sandy and silty soil and further possible groundwater contamination is still unclear and not fully understood in the literature. The present study focuses on the movement of High-Density Polyethylene (HDPE) microplastics in quartz sand and silty soil using column experiments. Detailed flow through laboratory experiments are performed to understand the effect of varying the critical parameters in contaminant transport such as pore volumes (1PV,2PV,3PV,4PV,5PV,6PV,7PV,8PV,9PV,10PV) and flow rates (20,40,60,80,100,120 ml/min) on HDPE microplastic movement in sandy and silty soil separately. The maximum depth of microplastic transport in sandy soil was 20-22 cm for a flow rate of 120 ml/min, and 10-12 cm for 20 ml/min. In silty soil, the maximum depth of microplastic transport was 12-14 cm for 120 ml/min and 6-8 cm for 20 ml/min. The study also estimates the number of years required for microplastic contamination to reach groundwater under field conditions by considering the L/S ratio. The study estimated that it could take 144 years for microplastics to penetrate sandy soil and 356 years for silty soil, under the study conditions. The study highlights the significant threat posed by microplastics to groundwater contamination. The results suggest that soils may serve as both a sink for microplastics and a potential pathway for their entry into subsurface environments, such as underground habitats and water sources.